Thomas Hobbes: a opinião tutelada como antídoto ao poder das trevas - Coelho, Francisco Sérgio Marçal (2018)
The purpose of this thesis is to highlight Thomas Hobbes' effort to neutralize the power of the clergy and to establish control over opinions, particularly the ones that disaggregates the social order, so as to guarantee the permanence of the sovereign power after the establishment and during the validity of the social contract. In Hobbes view, after the establishment of the social pact and of the conditions to overcome the state of nature, it was still necessary to fight against the intestinal agents of sedition who continued to act in a way that caused a real danger of a return to the state of war of all against all. It will be shown in addition that the peculiar Hobbesian interpretation of the Holy Scriptures, sought to reassure the absolute power as a means to eliminate the potential danger of social upheaval which he attributed to the generality of the clergy. For Hobbes, the clergy behaved as a parallel power manipulating human passions and preaching spurious doctrines that were conducive to social disaggregation. It is worth, still, to point out that he proposed the control of potentially dissident opinions and the replacement of the curricula of universities that he deemed contaminated by the disintegrative influence of the scholastic. He saw such a control as the only effective antidote to immunize the State against what he judged to be the power of darkness and to guarantee the stable exercise of sovereignty in the hands of the legitimate representative established in the social pact.